POZYCJA PROCESOWA STRONY NA ETAPIE WSZCZĘCIA POSTĘPOWANIA ADMINISTRACYJNEGO - Gill, Artur (Wydział Prawa i Administracji UAM, 2003)
This paper presents a discussion of the complex procedural position of a party in administrative proceedings at the stage of instigating ordinary first instance proceeding. Unlike appellate proceedings, these proceedings can be instigated both upon a motion of a party and ex officio. Proceedings are initiated on the party’s motion if they seek to influence the party’s rights and therefore end in a decision granting a new right, extend the existing powers, lifting the present obligations or stating inexistence o f obligation. On the other hand, proceedings are instigated ex officio if in consequence of them some new obligations are imposed on the party, i.e. proceedings end in decisions imposing new obligations, extending already existent obligations, or stating the existence of certain obligations. The above lists of legal consequences of decisions ending first instance proceedings only serve as examples. The principle is clear: the party will demand an instigation of proceedings i f it is in its interests and it will remain passive if its interests are threatened.
PARTY’S PROCEDURAL POSITION AT THE STAGE OF ADMINISTRATIVE PROCEDURE INITIATION